The Frequency Causative Organisms and Their Sensitivity to the Commonly used Antibacterial Agents in Cases of Urinary Tract Infections (Medical Forum Monthly, 2024)
Objective: Frequency causative organisms and their sensitivity to the commonly used antibacterial agents in cases of urinary tract infections.Study Design: Observational studyPlace and Duration of Study: This study was conducted at Medical Wards of Civil Hospital Karachi from 1st November 2010 to 30th April 2011.Materials and Methods: This study consisted of 415 patients were selected for urine culture and sensitivity from medical O.P.D. and hospitalized patients in medical wards. Detailed history was taken from all the patients with special regard to symptoms and duration of UTI. Inclusion criteria were that all patients who had symptoms of urinary tract infection like frequency of micturition by day and night, painful voiding (dysuria), suprapubic pain and tenderness, hematuria, smelly urine, urgency , loin pain or swelling and patients who had more than 6 pus cells in urine D/R examination. Urine samples from OPD patients were randomly assigned to different reputable clinical pathological laboratories including pathological laboratory of Civil Hospital, Karachi, for urine culture and sensitivity.Results: 415 patients 265(63.8%) were females and 150(36.2%) were males. 415 urine samples who were subjected to urine culture and sensitivity examination. Only 200 (48.2%) samples were found to had infection i.e. significant growth of 105 of microorganism/ml or more, while 142 (34.2%) samples did not show growth of any organism, and 73 (17.6%) samples showed growth between 104 and 105 of microorganism/ml . E. Coli 49.5% is the commonest organism causing UTIs in outpatients as well as in hospitalized patients. The second commonest organism in OPD is Klebsiella 16%, while in hospitalized patients it is Pseudomonas. The antibiotics susceptibility of the isolated organisms during the study and shows the percentage of sensitivity of the isolated organisms. E. coli the most common organism isolated showed high resistance pattern to ampicillin, amoxicillin, and co-trimoxazole 62%, 60%, 70%, respectively. E. coli the most common organism isolated showed a high sensitivity pattern to amoxicillin/clavulanic acid 85%, pipemidic acid 80%, norfloxacin 85%, ofloxacin 92%, ciprofloxacin 90%, tobramicin 98%. Generally a higher percentage of the organisms isolated were sensitive to all these antibiotics except amoxicillin/clavulanic acid which had a high resistance pattern to Pseudomonas 77%.Conclusion: Escherichia coli is still the commonest organism causing urinary tract infection, in outpatients as well as in hospitalized patients.